A Modified Design of Class-E Power Amplifier with Balanced FETs and High Output Power for RFID Applications - Zahid, Muhammad Noaman; Jiang, Jianliang; Lu, Heng; Zhang, Hengli (Proceedings of Engineering and Technology Innovation, 2021)
In Radio Frequency (RF) communication, a Power Amplifier (PA) is used to amplify the signal at the required power level with less utilization of Direct Current (DC) power. The main characteristic of class-E PA is sturdy nonlinearity due to the switching mode action. In this study, a modified design of class-E PA with balanced Metal Oxide Semiconductor Field Effect Transistors (MOSFETs) and high output power for Electronic Article Surveillance (EAS) Radio Frequency Identification (RFID) application is presented. MOSFETs are adjusted to have high output performance of about 80% for RFID-based EAS system. A matching network is also proposed for accurate matching because there are differences in the behavior between RF waves and low frequency waves. The design of a matching network is a tradeoff among the complexity, adjustability, implementation, and bandwidth for the required output power and frequency. The implemented PA is capable of providing 44.8 dBm output power with Power-Added Efficiency (PAE) of 78.5% at 7.7 MHz to 8.7 MHz.